Pengaruh Lingkungan Kerja terhadap Kelelahan Kerja, Tingkat Konsentrasi, dan Kualitas Tidur - Ferdi Firmansyah; Am Maisarah Disrinama; Farizi Rachman (Jurnal Ilmiah Kedokteran dan Kesehatan, 2025)
This study evaluates the impact of noise and work climate conditions on the level of work fatigue, concentration, and sleep quality of machine operators in the plastic sack industry in East Java. Based on measurement data from the Balai HIPERKES, the noise intensity in the work area reached 91.7 dB which exceeded the threshold, while work climate measurements had never been carried out. The analysis method applied in this study was Two Way MANOVA involving 93 respondents using a Sound Level Meter, WBGT Meter, and a questionnaire on work fatigue, concentration level, and sleep quality. The results of data processing showed that noise and work climate had a significant effect on work fatigue, concentration level, and sleep quality. A noisy and hot work environment can increase fatigue, decrease concentration, and worsen the sleep quality of machine operators. These findings indicate the importance of improving the work environment to maintain employee welfare and support productivity.